Meningkatkan Kemampuan Berbicara Anak Usia Empat Sampai Lima Tahun Melalui Media Pop-Up Book - Rizki Lestari, Anggraeni; Kurnia, Aam; Nursihah, Arif (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2022)
The background of this research is motivated regarding children's speaking which is still low. The number of children experience the difficulty in speaking due to the pronunciation of the letters and words which is unclear. The purpose of this study is to know the children's speaking ability, before, in process, and after using the pop-up book media in every cycle in group A at RA Widuri Asy-Syifa Cinanjung, Tanjungsari, Sumedang. The approach uses in this study is mixed-method design which is combining the quantitative and qualitative approach. The method that uses by the researcher is Classroom Action Research. This research consisted of two cycles and each cycle consisted of planning, implementing, observing and reflecting. The data collection technique of this research using observation, documentation and performance. The data analysis of this research using descriptive and statistics. The result of the study showed that children's speaking ability before using pop-up book media obtained an average value of 56 with less criteria. The process of implementing pop-up book media showed an increase, the teacher activity in cycle I is 75% and cycle II is 90%. The activity of the first cycle of children is 68% and the second cycle is 88%. Therefore, the children's speaking ability after implementing pop-up book media has increased, cycle I the average value is 67 and cycle II the average value is 85. Thus, the hypothesis proposed is accepted, therefore using pop-up book media can improve children's speaking ability